DİJİTAL ÇAĞDA SOSYAL ALGORİTMALAR: YAPAY ZEKÂ VE SOSYAL HİZMET. - BAŞCILLAR, Mehmet; KARATAŞ, Mustafa; PAK GÜRE, Merve Deniz (Journal of Social Policy Studies / Sosyal Politika Çalismalari Dergisi)
Artificial intelligence is software and hardware that imitates human intelligence and can improve itself with the information it obtains. Artificial intelligence has the potential to create new problems and solutions in life dynamics. The social work is in an effort to respond to this transformation. Focusing on various aspects of the interaction between artificial intelligence and social work, this study aims to provide a critical perspective on how social work interventions will be affected, and what the potential opportunities and risks may be. Among the opportunities in artificial intelligence-based social work practices are easily accessible, cost-effective, fast, and revised studies depending on the needs of the person. Risks include damage to the therapeutic relationship between the social worker and the client system, failure to develop sufficient and high-quality data feed for machine learning, ethical problems, and reduced need for social workers. As a result, it is recommended to develop artificial intelligence applications that are sensitive to both the professional stance of the social work and the rights of the client system.